Diferenciacija v šoli - Marjanovič Umek, Ljubica (Sodobna pedagogika, 2007)
Taking account of certain theoretical findings and results of foreign and domestic empirical researches, the article analyses individual changes introduced into the nine-year primary school in the last two years. We want to know what these changes mean in terms of the coherence of systemic and substantive solutions, as established in the concept laid down in the White paper on education (1995) and implemented in the Primary school act of 1996, and to what extent they are scientifically justified. We chose two types of changes especially referring to differentiation at school, namely changes in ability grouping and changes in the external assessment of knowledge - with the latter we were primarily interested in differentiation with regard to gender. Within the first research involving over 400 adolescents from the 9th grade of primary school, we found that two important criteria in the classification of pupils into individual levels of education were the adolescents' speech competence and their intellectual abilities, which are also otherwise the best predictors of the knowledge of a student. The mother's level of education had a smaller effect on the classification of pupils than the abovementioned psychological characteristics of the adolescents. The findings of the second research, involving pupils of 3rd and 4th grades, along with pupils of the 9th grade of the nine-year primary school, show that younger and older girls achieve significantly higher grades than boys in almost all subjects at school when their knowledge is assessed by teachers; however, in external knowledge assessments the differences between girls and boys with older pupils are only significant in the Slovenian language. Since the achievemnts in the national examination of knowledge are not one of the criteria for enrolment in secondary schools with limited enrolment, this creates additional injustice in the assessing of knowledge with regard to gender.
Keywords: nivojski pouk; diferenciacija; ocenjevanje znanja; zunanje ocenjevanje znanja; osnovne šole; razlike med spoloma